Characteristic 3D foot motion patterns during gait of patients with Charcot-Marie-Tooth identified by cluster analysis - Schmidt, Selena; Böhm, Harald; Dussa, Chakravarthy U.; Bienias, Katarzyna; Fujak, Albert (Gait & Posture, 2023)
Background: CMT is a clinically and genetically heterogenous disease with varying degrees of progression. Different foot deformities, gait and movement patterns are observed. In order to achieve an improved, targeted treatment strategy, the participants are divided into characteristic groups using a mathematical cluster analysis based on the data from the three-dimensional foot kinematics during walking. Methods: Outpatients from age 5–64 years (N = 33 participants, 62 feet) with a proven CMT type 1 (N = 16, 31 feet) or CMT without any further type assignment (N = 17, 31 feet) were retrospectively analyzed. After a standard clinical examination, participants underwent 3D gait analysis using the Oxford Foot Model. To classify the movement patterns, a k-means cluster analysis was calculated based on the principal component analysis (PCA) of the foot kinematics data. Gait parameters, clinical parameters and X-ray data were statistically tested. Results: The cluster analysis divided the gait data of the participants into two groups. Cluster 1 (N = 21 participants, 34 feet) showed increased dorsiflexion of the hindfoot and increased plantarflexion of the forefoot with cavus position in the sagittal plane, a hindfoot inversion and forefoot pronation with hindfoot varus in the frontal plane and in the transversal plane a forefoot adduction. Cluster 2 (N = 17 participants, 28 feet) deviated significantly from the norm mainly in the frontal plane and were characterized by a strong eversion of the hindfoot with a supination in the forefoot. Discussion: Based on the findings, the resultant clusters can be interpreted as cavovarus feet (cluster 1) and pes valgus (cluster 2). The most reliable variables in the 3D gait analysis to classify CMT feet with regard to significance are the ones in the frontal plane. This subdivision of participants goes hand in hand with the various necessary guidelines for orthopedic treatment.
CRIS-Team Scopus Importer:2023-07-21
Keywords: 3D gait analysis; Cavovarus foot; Classification; CMT; Pes valgus

Does an overcorrected clubfoot caused by surgery or by the Ponseti method behave differently? - Dussa, Chakravarthy U.; Böhm, Harald; Döderlein, Leonhard; Forst, Raimund; Fujak, Albert (Gait & Posture, 2020)
Background: Overcorrection is a recognized problem following surgical treatment of congenital clubfoot. Recently this complication has also been mentioned following Ponseti treatment. Research question: Do overcorrected clubfeet (OCCF) caused by surgery behave differently from those caused by Ponseti treatment in terms of segmental motion of the feet and show differences in the severity of deformity on X-rays? Methods: Children between 7 and 12 years with OCCF were included in this study. Depending on the aetiology causing them, the feet were divided into 2 groups (Ponseti and peritalar release surgery). 25 typically developing children served as controls. All subjects were subjected to clinical and radiological examination and 3-Dimensional gait analysis using the Oxford Foot Model. Results: Thirty-two children with OCCF, of these 18 feet in the surgical and 14 feet in the Ponseti group, were included in the study. No radiological differences were seen in the flatfoot parameters between OCCF groups except in the calcaneal inclination angle that was more pathological in the Ponseti group. The clinical ankle plantar flexion was significantly reduced in the surgical group. During walking the range motion of the hindfoot in the frontal plane was significantly reduced in surgically treated feet compared to the Ponseti group. The other parameters did not show any significant difference between groups. Significance: The overcorrected clubfeet following surgery and Ponseti showed similar appearance and showed no significant differences in 11/12 radiological parameters. The segmental motion of the feet showed no significant differences between groups except the in the range of motion of the subtalar eversion. A considerable subtalar joint motion was present even in the surgical group. These findings might help plan the treatment of these feet.
CRIS-Team Scopus Importer:2020-03-10
Keywords: Flatfeet; Idiopathic clubfeet; Overcorrection; Ponseti; Surgery

Hereditary Muscle diseases - Fujak, Albert; Forst, Raimund; Forst, Juergen (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2022)
Stellvertretend fur die gro ss e Gruppe der erblichen Muskelerkrankungen stellen wir in dieser ubersicht diejenigen Erkrankungen vor, die in einer spezialisierten orthopadischen Sprechstunde am haufigsten anzutreffen sind und fur die bereits eine ausreichende Erfahrung in der konservativen und operativen orthopadischen Therapie zur Verfugung steht.
CRIS-Team WoS Importer:2022-07-29

Is shortening of Tibialis Anterior in addition to calf muscle lengthening required to improve the active dorsal extension of the ankle joint in patients with Cerebral Palsy? - Dussa, Chakravarthy U.; Böhm, H.; Döderlein, Leonhard; Fujak, Albert (Gait & Posture, 2021)
Introduction: Shortening of the tibialis anterior tendon (TATS) has been shown to improve the ankle dorsiflexion in swing following the calf muscle lengthening procedure (CMLP) in patients with cerebral palsy (CP). Others have reported the similar improvements following CMLP but without TATS. However there are no studies comparing both procedures. Therefore the purpose of the study was to compare the ankle dorsiflexion in swing and foot position in the sagittal plane during gait following TATS and CMLP to that of CMLP alone. Materials and methods: A retrospective study was carried out in CP patients who presented with fixed equinus deformity. They were grouped into unilateral CP and bilateral CP. Depending on the procedures, each group was again subdivided into subgroup CMLP only and subgroup CMLP and TATS (CMLPTATS). All patients were subjected to pre and postoperative clinical and gait analysis. Results: 44 feet in 44 patients were included in the study. Of these, 24 feet (24 patients) belonged to unilateral and 20 feet (20 patients) to bilateral CP group. The mean age of the patients at surgery was 11.5 years (6.0 – 29.0) in the unilateral CP group and 10.5 years (5.0-34.0) in the bilateral CP group. In the unilateral CP group, 12 feet belonged to subgroup CMLP and 12 to subgroup CMLPTATS with a mean equinus contracture of 7.5° in both subgroups. In bilateral CP group, 11 feet belonged to subgroup CMLP with a mean equinus contracture of 5° and 9 to subgroup CMLPTATS, with a mean equinus contracture of 10°. The subgroups did not vary significantly in the demographics, anthropometry, kinematics and kinetics of ankle joint preoperatively. The mean follow up time was 19.7 months. The surgery produced significant changes in both groups and subgroups. However, none of the relevant gait parameters were significantly different between groups and subgroups. Significance: Adding TATS to CMLP, compared to CMLP alone did not improve ankle dorsiflexion in swing and the foot position more than CMLP alone.
CRIS-Team Scopus Importer:2020-11-27
Keywords: bilateral; Cerebral palsy; equinus contracture; tibialis anterior; unilateral

Is the conservative treatment of sacral insufficiency fractures still up to date? Retrospective clinical observational study in 46 patients - Schramm, Simon; Kopschina, Carsten; Gaßmann, Karl Günter; Fujak, Albert (Orthopaedics & Traumatology-Surgery & Research, 2023)
Background: According to current forecasts, our society will grow older and older, so that the proportion of 6% of the German population from 2017 who were 80 years or older will increase further. The frequency of falls in this patient population lead to a further increase of sacral insufficiency fractures. Hypothesis: The aim of this study is to evaluate the multimodal interdisciplinary conservative therapy regime for sacral insufficiency fractures in geriatric patients, especially on the basis of mobility and the need for assistance. Patients and Methods: A cohort of patients, who were treated as inpatients at the Waldkrankenhaus St. Marien in Erlangen with ICD-10 for sacral fractures S32.1 as the main diagnosis, was retrospectively examined. Only newly diagnosed sacral insufficiency fractures were taken into account. Patients were divided into groups based on the factors hospital stay, fracture location on the sacrum, and location of concomitant pelvic ring injury. The Barthel Index, the Tinetti's Mobility Test and the Timed Up&Go Test were recorded. Results: 46 patients met the inclusion criteria. Using the conservative therapy, improvements were achieved in all patients in terms of need for care, mobility without aids and risk of falling, also patients with an anterior and posterior pelvic ring fracture. Regard a score improvement in the Barthel Index and Tinetti Mobility Test, patients with bilateral sacral insufficiency fracture (n = 17, 37.0%) did not differ significantly from patients with unilateral sacral insufficiency fracture (n = 22, 47.8%). Conclusion: In geriatric patients, decisions about therapy should always be made on an individual and interdisciplinary basis. The conservative therapy regimen continues to play an important role in this. The collected tests–consisting of Barthel Index, Tinetti Mobility Test and Timed Up&Go Test–are well suited for further reproducible, objective studies with a larger patient collective. Level of evidence: IV.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Fragility Fractures of the Pelvis; geriatric medicine; Sacral insufficiency fracture

Is the conservative treatment of sacral insufficiency fractures still up to date? Retrospective clinical observational study in 46 patients - Schramm, Simon; Kopschina, Carsten; Gaßmann, Karl-Günter; Fujak, Albert (Revue de Chirurgie Orthopedique et Traumatologique, 2023)
Background: According to current forecasts, our society will grow older and older, so that the proportion of 6 % of the German population from 2017 who were 80 years or older will increase further. The frequency of falls in this patient population lead to a further increase of sacral insufficiency fractures. Hypothesis: The aim of this study is to evaluate the multimodal interdisciplinary conservative therapy regime for sacral insufficiency fractures in geriatric patients, especially on the basis of mobility and the need for assistance. Patients and methods: A cohort of patients, who were treated as inpatients at the Waldkrankenhaus St. Marien in Erlangen with ICD-10 for sacral fractures S32.1 as the main diagnosis, was retrospectively examined. Only newly diagnosed sacral insufficiency fractures were taken into account. Patients were divided into groups based on the factors hospital stay, fracture location on the sacrum, and location of concomitant pelvic ring injury. The Barthel Index, the Tinetti's Mobility Test and the Timed Up&Go Test were recorded. Results: Forty-six patients met the inclusion criteria. Using the conservative therapy, improvements were achieved in all patients in terms of need for care, mobility without aids and risk of falling, also patients with an anterior and posterior pelvic ring fracture. Regard a score improvement in the Barthel Index and Tinetti Mobility Test, patients with bilateral sacral insufficiency fracture (n = 17, 37.0 %) did not differ significantly from patients with unilateral sacral insufficiency fracture (n = 22, 47.8 %). Conclusion: In geriatric patients, decisions about therapy should always be made on an individual and interdisciplinary basis. The conservative therapy regimen continues to play an important role in this. The collected tests – consisting of Barthel Index, Tinetti Mobility Test and Timed Up&Go Test – are well suited for further reproducible, objective studies with a larger patient collective. Level of evidence: IV.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Fragility fractures of the pelvis; Geriatric medicine; Sacral insufficiency fracture

Is there a correlation between static radiographs and dynamic foot function in pediatric foot deformities? - Böhm, Harald; Döderlein, Leonhard; Fujak, Albert; Dussa, Chakravarty U. (Foot and Ankle Surgery, 2019)
Background: Idiopathic flexible flatfeet, congenital clubfeet and pes cavovarus are the most common foot deformities in children. Accurate assessment to quantify the severity of these deformities by clinical examination alone can be challenging. Radiographs are a valuable adjunct for accurate diagnosis and effective treatment. However, static radiographs during relaxed standing may not reflect the dynamic changes in the foot skeleton during functional activities such as walking. Therefore, the aim of this study is to predict dynamic foot movements during walking from planar standing radiographs to reveal the significance of the radiographic analysis for the assessment of foot function. Methods: Patients 8–17 years with flexible flatfeet (FFF, n = 217) recurrent clubfeet (RCF n = 38) and overcorrected clubfeet (OCCF, n = 71) of non-neurogenic or syndromic origin and pes cavovarus due to peripheral neuropathy (PNP, n = 48) were retrospectively included. Patients underwent gait analysis with the Oxford Foot Model and radiographic examination in anterior-posterior and lateral view during standing. Multilinear predictor analysis of selected gait parameters was performed based on radiographic measures. Results: The variance that was explained by radiography was greatest for the transverse plane forefoot abduction with 33% for OCCF, 50% for RCF and 59% for PNP. Flatfeet and foot kinematics in the other planes or between rearfoot and tibia showed little or no relation. Conclusions: The static measures of foot deformities by radiography could explain only a small amount of variance in foot kinematics during walking, in particular for FFF. An explanation may be that the forces during weight bearing bear little resemblance to those during gait in terms of neither magnitude nor direction. These findings suggest that foot function cannot be accurately assessed solely from static radiographic observations of the foot, commonly undertaken in clinical practice.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Clubfeet; Flat feet; Foot deformities; Pes cavovarus; Radiographs; Walking

Long-term Results of Conservative Therapy of Adolescent Idiopathic Scoliosis Using the Cheneau Brace - Weniger, Carmen Dorothea; Fujak, Albert; Hofner, Benjamin; Fuchs, Markus; Forst, Raimund; Richter, Richard Heinrich (Klinische Pädiatrie, 2019)
Adolescent idiopathic scoliosis is a disease of the growing skeleton. The goal in therapy is to decelerate or to prevent progression of the spinal curve. As part of a retrospective study the patient group of the scoliosis surgery from 1995-2016 was analysed according to the inclusion criteria of the Scoliosis research Society (SRS). 159 of 643 of the patients fullfilled the specific criteria. The assessment of effectiveness was based on the progression of the angle of curvature. If it was ≤5° it was judged positively. The therapy in accordance to Cheneau is a full-time bracing orthosis. Data from 159 patients - 136 fem. (85.5%), 23 male (14.5%) was analysed. The average age at the beginning of treatment was 13.3±1.7 years. The average duration was 3.47±1.2 years. The average Cobb-angle before treatment was 28.39°±9.44°. At the completion is was 27.7°±12.34°. Stabilisation of scoliosis (≤5°) was achieved for 136 of the patients (85.5%). The final follow-up showed a progression of the Cobb angel>5° in 23 cases, of which 19 had to undergo secondary surgery. The length of therapy had a positive influence (p=0.057) on the result. Brace treatment constitutes an effective method of therapy at curvatures between 20-40°. Short duration of therapy correlates with a expressively increased risk towards progression (p=0.057). The Cheneau brace treatment constitutes an effective treatment at curvature angles between 20-40°. The risk of progression can be reduced by a timely and correct identification.
CRIS-Team Scopus Importer:2019-09-17

Orthotic Care Based on the Ferrari Concept for Children and Adults with Meningomyelocele - Schmid, Tim; Strehl, Elisabeth; Trollmann, Regina; Forst, Raimund; Fujak, Albert (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Background Even today, myelomeningocele (MMC) is still encountered in clinical medicine and its incidence has not decreased over the last 20 years despite a known reduction in risk due to the use of folic acid supplements. The spectrum of clinical symptoms is extremely broad and, depending on the level of the defect, varies from mild to severe. Subject to the degree of paralysis, patients are reliant on the use of orthopaedic aids and orthoses for the treatment of primary contractures and deformities and the prevention of secondary ones. This forms the basis for attaining or maintaining mobility in many patients. The objective of the study was to determine the practical application of the proposed Ferrari concept for the provision of orthoses for children and adults. Patients and Material The retrospective study comprised medical records of 180 patients (97 m) with an average age of 19.44 years (3-52 years, SD 9.3) at the time of investigation. The average duration of treatment was 15.34 years (1-38 years, SD 8.96). Data relating to deformities of the vertebral column and lower limbs, provision of hydrocephalus shunts and orthoses, and patient mobility was evaluated. Results Most patients were given systematic treatment with orthoses at an early stage. In 58,9% of cases, it was possible to implement the proposed concept for providing patients with dynamic orthoses, whereby the treatment concept was more difficult to implement with high lumbar lesions than with lower lesions. Moreover, a decrease in the patients' mobility with increasing age was noticeable. Some 42.3% of adult patients were able to walk with marked variations in mobility in relation to the different levels of lesions. Conclusion Taking into consideration the complexity of both the clinical picture and therefore the provision of orthopaedic devices, the result of the implementation of the proposed orthotic concept can be considered positive. Similarly, early commencement of provision of orthoses and hence the possibility of achieving a positive influence on later mobility can be considered a success. The need for individual concepts and further development in order to increase mobility particularly in the case of patients with thoracic or high lumbar lesions is evident. A more comprehensive provision of information to patients regarding orthotic treatment options and their consequences for prophylaxis and quality of life should be an important component of interdisciplinary long-term patient care.
CRIS-Team Scopus Importer:2019-12-13
Keywords: MMC; mobility; orthopaedic treatment concept; orthotics

Poliomyelitis (Poliomyelitis acuta, Kinderlähmung, Heine-Medin-Krankheit) - Fujak, Albert (Zeitschrift für Gastroenterologie, 2023)
CRIS-Team Scopus Importer:2023-12-29

Treatment of spastic varus/ equinovarus foot with split-tendon transfers in cerebral palsy: How does it affect the hindfoot motion? - Dussa, Chakravarthy U.; Böhm, Harald; Döderlein, Leonhard; Fujak, Albert (Gait & Posture, 2022)
Introduction: The flexible spastic varus foot in cerebral palsy is commonly corrected by split-tendon transfer of tibialis anterior or tibialis posterior. These tendon transfers are said to preserve hindfoot motion, which is until now not been proven. Therefore, the aim of the study was to show the hindfoot motion following split-tendon transfer in comparison to a midtarsal arthrodesis. Materials and methods: A retrospective study was done on patients with flexible spastic varus foot in cerebral palsy who underwent a combined split-tendon transfer of tibialis anterior and posterior. Patients with a rigid foot deformity underwent a midfoot arthrodesis. These children and normal children served as controls. An instrumented gait analysis was done in all patients before and at follow-up. A statistical analysis was done using 2-factor ANOVA with repeated measures on time. Results: Thirteen children underwent a combined split-tendon transfers of tibialis anterior and posterior muscles and 14 children midtarsal arthrodesis. The mean follow-up was 2.4 (SD=0.8) years for flexible varus foot and 1.9 (SD=0.7) years for rigid foot deformity. The preoperative hindfoot range of motion in eversion-inversion was 54% and 49% of TD controls in flexible varus foot and rigid foot deformity respectively. At follow-up, it reduced further to 45% and 42% of TD controls in the respective groups. Conclusion: Both flexible and rigid hindfoot deformity reduced the hindfoot motion. However following surgery, the hindfoot motion reduced further and was identical in both groups independent of the type of surgery. This indicates a tenodesis-effect of split-tendon transfers on the hindfoot.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Cerebral palsy; Chopart arthrodesis; Hindfoot kinematics; Midtarsal arthrodesis; Spastic varus/equinovarus foot; SPLATT; Split-tendon transfers; SPOTT; Tibialis anterior; Tibialis posterior